The Effect of Combined Oral Contraceptives on Sexual Function among Women of Reproductive Age in Jombang District, East Java - Fatmawati, Zeny; Budihastuti, Uki Retno; Dewi, Yulia Lanti Retno (Journal of Maternal and Child Health, 2017)
Background: Sexuality is an important and inseparable part of a woman's life. Mood and sexual related side-effects are frequently expressed problems by women of reproductive age who use hormonal contraceptives. This study aimed to analyze the effect of combined oral contraceptives on sexual function among women of reproductive age in Jombang District, East Java. Subjects and Method: This was an analytic observational study using cross-sectional design. The study was conducted at 5 community health centers (Mojoagung, Mojowarno, Jogoloyo, Jelak Ombo and Perak), Jombang District, East Java, from February to March 2017. A sample 120 women of reproductive age who use combined oral contraceptives was selected for this study. The dependent variable was female sexual function. The independent variables were combined oral